Family Firms and Financial Performance: The Cost of Growing (2011)
This study examines the relationship between financial performance and family involvement for 523 listed and non-listed Colombian firms from 1996-2006. Using a detailed database and performing several panel data regression models, we have found that family firms exhibit better financial performance on average than non-family firms when the founder is still involved in operations, although this effect decreases with firm size. With heirs in charge, there is no statistical difference in financial performance. Both direct and indirect owner-ship (control through pyramidal ownership structures within family business groups) affect a firm's financial performance positively. However, this positive effect decreases with firm size, and some kinds of family involvement appear to make firm growth expensive.